10th Anniversary of ALPPS—Lessons Learned and quo Vadis. Issue 1 (January 2019) - Lang, Hauke; de Santibañes, Eduardo; Schlitt, Hans J.; Malagó, Massimo; van Gulik, Thomas; Machado, Marcel A.; Jovine, Elio; Heinrich, Stefan; Ettorre, Giuseppe Maria; Chan, Albert; Hernandez-Alejandro, Roberto; Robles Campos, Ricardo; et al.
Abstract : Objective: Associating Liver Partition and Portal vein ligation for Staged hepatectomy (ALPPS) has been tested in various indications and clinical scenarios, leading to steady improvements in safety. This report presents the current status of ALPPS. Summary Background Data: ALPPS offers improved resectability, but drawbacks are regularly pointed out regarding safety and oncologic benefits. Methods: During the 12th biennial congress of the European African-Hepato-Pancreato-Biliary Association (Mainz, Germany, May 23–26, 2017) an expert meeting "10th anniversary of ALPP" was held to discuss indications, management, mechanisms of regeneration, as well as pitfalls of this novel technique. The aim of the meeting was to make an inventory of what has been achieved and what remains unclear in ALPPS. Results: Precise knowledge of liver anatomy and its variations is paramount for success in ALPPS. Technical modifications, mainly less invasive approaches like partial, mini- or laparoscopic ALPPS, mostly aiming at minimizing the extensiveness of the first-stage procedure, are associated with improved safety. In fibrotic/cirrhotic livers the degree of future liver remnant hypertrophy after ALPPS appears some less than that in noncirrhotic. Recent data from the only prospective randomized controlled trial confirmed significant higher resection rates in ALPPS with similar peri-operative morbidity and mortality rates compared with conventional 2-stage hepatectomy including portal vein embolization. ALPPS is effective reliably even after failure of portal vein embolization. Conclusions: Although ALPPS is now an established 2-stage hepatectomy additional data are warranted to further refine indication and technical aspects. Long-term oncological outcome results are needed to establish the place of ALPPS in patients with initially nonresectable liver tumors.